Comparative Effectiveness of Zinc Supplementation Combined with Probiotic Therapy Versus Zinc Alone in Reducing Acute Diarrhea Duration, Severity, and Recurrence Rates in Pediatric Populations: A Meta-Analysis - Raza, Wasiq; Mahmood, Talat; Atta, Lyaba; Hassan, Sualeh; Sami Ullah; Ali, Shahid; Mian Muhammad; Ahmad, Nigar (Indus Journal of Bioscience Research, 2024)
Background: Diarrhea remains a significant concern for children under five, particularly in developing countries. While zinc supplementation is a standard intervention for managing diarrheal diseases, the potential role of probiotics in restoring gut flora is gaining recognition. However, limited research has compared the efficacy of zinc alone versus zinc combined with probiotics. Objective: This meta-synthesis aimed to evaluate evidence from comparative studies to determine whether combining zinc with probiotics is superior to zinc alone in reducing the incidence, severity, and recurrence of diarrhea in children. Methods: A systematic review of 24 studies published in English, including 18 randomized controlled trials (RCTs) and six observational studies, was conducted following PRISMA guidelines. The focus was on children aged 0–12 years with acute diarrhea. Outcomes assessed included fecal and diarrheal frequency, episode duration, and relapse rates within three months. Standardized mean differences (SMDs) and odds ratios (ORs) were calculated for quantitative synthesis. Results: Combination therapy significantly reduced diarrhea duration by 1.25 standard deviations (p < 0.001) and recurrence rates by a factor of 0.65 (p = 0.002) compared to zinc monotherapy. Notably, Saccharomyces boulardii and Lactobacillus rhamnosus GG exhibited the highest efficacy. Sensitivity analysis confirmed the robustness of these findings. Conclusion: Probiotics enhance the effectiveness of zinc in managing acute diarrhea in children. These findings support incorporating combination therapy into pediatric care globally, aligning with public health recommendations to improve outcomes for children